Molecular characterization of TGF-β type I receptor gene (Tgfbr1) in Chlamys farreri, and the association of allelic variants with growth traits. - Huihui Guo (Public Library of Science (PLoS), 2012)
Background Scallops are an economically important aquaculture species in Asian countries, and growth-rate improvement is one of the main focuses of scallop breeding. Investigating the genetic regulation of scallop growth could benefit scallop breeding, as such research is currently limited. The transforming growth factor beta (TGF-β) signaling through type I and type II receptors, plays critical roles in regulating cell proliferation and growth, and is thus a plausible candidate growth regulator in scallops. Results We cloned and characterized the TGF-β type I receptor (Tgfbr1) gene from Zhikong scallops (Chlamys farreri). The deduced amino acid sequence contains characteristic residues and exhibits the conserved structure of Tgfbr1 proteins. A high expression level of scallop Tgfbr1 was detected during early embryonic stages, whereas Tgfbr1 expression was enriched in the gonad and striated muscle in adults. A single nucleotide polymorphism (SNP, c. 1815C>T) in the 3' UTR was identified. Scallops with genotype TT had higher growth traits values than those with genotype CC or CT in a full-sib family, and significant differences were found between genotypes CC and TT for shell length, shell height, and striated muscle weight. An expression analysis detected significantly more Tgfbr1 transcripts in the striated muscle of scallops with genotype CC compared to those with genotype TT or CT. Further evaluation in a population also revealed higher striated muscle weight in scallops with genotype TT than those with the other two genotypes. The inverse correlation between striated muscle mass and Tgfbr1 expression is consistent with TGF-β signaling having a negative effect on cell growth. Conclusion The scallop Tgfbr1 gene was cloned and characterized, and an SNP potentially associated with both scallop growth and Tgfbr1 expression was identified. Our results suggest the negative regulation of Tgfbr1 in scallop growth and provide a candidate marker for Zhikong scallop breeding.